The politics of distributing blame and credit: Evidence from a survey experiment with Norwegian local politicians - SCHÖNHAGE, NANNA LAURITZ; BÆKGAARD, MARTIN; GEYS, BENNY (European journal of political research, 2024)
How do politicians attribute responsibility for good and poor policy outcomes across multiple stakeholders in a policy field where they themselves can affect service provision? Such ‘diffusion’ decisions are crucial to understand the political calculations underlying the allocation of blame and credit by office‐holders. We study this issue using a between‐subjects survey experiment fielded among local politicians in Norway (N = 1073). We find that local politicians attribute responsibility for outcomes in primary education predominantly to school personnel (regardless of whether performance is good or bad) and do not engage in local party‐political blame games. However, we show that local politicians are keen to attribute responsibility for poor outcomes to higher levels of government, especially when these are unaligned with the party of the respondent. These findings suggest that vertical partisan blame‐shifting prevails over horizontal partisan blame games in settings with a political consensus culture.